A new method to determine the crack closure stress based on stress difference. (June 2022) - Xie, Shijie; Han, Zhenyu; Shu, Ronghua; Chen, Yifan; Feng, Fan
Highlights: A new method is proposed to identify the crack closure stress under compression. The method gets rid of subjectivity and is easy to be applied. The accuracy of the new method is verified by the comparison with the existing methods. Abstract: Crack closure stress is a key stress threshold of rocks under compression, the determination of which is of great significance to the evaluation of macroscopic deformation behavior and microscopic fracture evolution characteristics of rocks. Based on the applicability and analysis of the existing methods, a novel method called axial stress difference (ASD) method on the basis of axial stress - axial strain curve is proposed. This method reduces the dependence on the elastic modulus which restricts the promotion of previous methods, and can objectively acquire the crack closure stress by the identification of the onset point of linearly elastic stage of axial stress - axial strain curves. Then, the crack closure stress of rock materials under uniaxial and triaxial compression obtained by the ASD method is compared with the counterparts from other methods. The results obtained by the ASD method are close to that by other methods, which can also be verified by the small standard deviation and coefficient of variation. Since the International Society for Rock Mechanics and Rock Engineering (ISRM) has not yet recommended standard methods for solving the crack closure stress, this method can be an effective supplement to the existing methods.